Evaluating the cost-effectiveness of testing pregnant women for penicillin allergy. - Viengneesee Thao; Emily E Sharpe; Ruchita Dholakia; Hannah H Ahn; James P Moriarty; Bijan J Borah; Margaret C Gill; Regan N Theiler (PLoS ONE, 2023)
Introduction True penicillin allergy is rare and is commonly incorrectly reported. In fact, less than five percent of patients who report a penicillin allergy will have a currently active clinically-significant IgE- or T-cell-mediated hypersensitivity when appropriately tested. Penicillin is the agent of choice for intrapartum antibiotic prophylaxis to reduce the risk of group B streptococcus early-onset disease in the newborn. Inaccurate penicillin allergy status may lead to inappropriate antibiotic use, as most alternative drugs are more expensive and broader spectrum than penicillin. Penicillin allergy testing has been found to be safe in pregnancy and cost-effective in other patient populations. Objective To evaluate the cost-effectiveness of penicillin allergy testing and appropriate antibiotic treatment (test then treat strategy) compared to usual care among pregnant women. Methods We developed a decision tree to evaluate the cost of providing appropriate care via a test then treat strategy for pregnant women who report a penicillin allergy, compared to usual care. Results Using the test then treat strategy the additional cost to ensure appropriate care for all pregnant women who report a penicillin allergy, was $1122.38 per person. Adopting a test then treat strategy increased the number of appropriate antibiotic use from 7,843/10,000 to 10,000/10,000 simulations. Conclusion Our results show that a test then treat strategy for pregnant women who report a penicillin allergy is a good-value intervention.